Two new species of the nemourid genus Amphinemura (Plecoptera: Nemouridae) from China - Li, Weihai; Du, Kaishu; Yang, Ding (Zootaxa, 2017)
Two new species of the nemourid genus Amphinemura, A. dabanshana sp. nov. and A. kuankuoshui sp. nov., are described from Qinghai and Guizhou provinces of China. These two new species are compared with related taxa. The types of the new species are deposited in the Entomological Museum of China Agricultural University, Beijing and Henan Institute of Science and Technology, Xinxiang, respectively.